Foreign Direct Investment or External Debt and Domestic Saving: Which has Greater Impact on Growth - Horas Djulius (ETIKONOMI, 2018)
The choice taken by developing countries in meeting the lack of development funds has a varying effect. This study clarifies the role of foreign direct investment (FDI) compared to foreign loans and domestic savings in short- and long-term economic growth of Indonesia. Data were obtained from World Bank and Bank Indonesia and used in error correction model to explain the linkage between predictors and economic growth. We show that in the short run, the three explanatory variables significantly affect economic growth. In the long run, compared to FDI and foreign loans, domestic savings positively and significantly affect economic growth. This study emphasizes the importance of sustaining domestic savings to maintain the stability of economic fundamentals in the long term.DOI: 10.15408/etk.v17i1.7120